The Relationship of Mental Toughness to Shooting Accuracy among Advanced Basketball Players - Ibrahim Bahram Khorshid Mohammed Ali (Pubmedia Jurnal Pendidikan Olahraga, 2025)
Examining the correlation between mental toughness and the accuracy of basketball shooting skills among advanced players is the key aim of the current study. The researcher employed the descriptive method by using the correlational approach, as it was the most appropriate for addressing the research problem. The research community was deliberately selected and consisted of advanced basketball players in Kirkuk Governorate, distributed across several clubs. The research sample was randomly selected by lottery and included 18 players from North Gas Basketball Club. The study found a statistically significant positive relationship between mental toughness and shooting accuracy among advanced basketball players, highlighting the importance of psychological factors in enhancing skill performance. Players with high mental toughness demonstrated greater confidence in decision-making during shooting, which was reflected in higher shot success rates. While psychological pressure and stress negatively affected shooting accuracy, mental toughness helped reduce the impact of these factors. The researcher recommends incorporating psychological training programs aimed at developing mental toughness among basketball players through exercises that focus on stress management and mental concentration. It is also suggested to adopt pressure-simulation methods during training to enhance players’ shooting accuracy under real-game conditions, and to encourage coaches to integrate techniques such as mental imagery and mindfulness meditation into training sessions to strengthen self-confidence and improve performance under pressure